(untitled) (Perner’s Contacts, 2008)
The paper is making analysis of factors, which user of transport service has on the mind, when he is judgeing expenses and profit from point of wiew of choice of transport system. The user in personal and load transport is perceive and evaluate above all price and time of transport too. Next meditated factors are reliability, fluentment and amenities of single sorts of transport in framework of transport system. The decision may be under influence positive and negative experiences and attitudes of the same user or experiences of other comparable subjects. The attitudes have three components: cognitive, affect and performance components. For decision is important agreement between attitudes of user and the other subjects, because official informations in offer or advertising may be in contradiction with system of attitudes. Subsequently the user is dealing according to performance component of this attitude, because he does defende to cognitive disonance.